Investigation of differential diffusion in lean, premixed, hydrogen-enriched swirl flames - Benjamin Francolini; Luming Fan; Ehsan Abbasi-Atibeh; Gilles Bourque; Patrizio Vena; Jeffrey Bergthorson (Applications in Energy and Combustion Science, 2024)
Hydrogen combustion is a promising alternative to fossil fuel combustion in an effort to reduce our carbon footprint. However, hydrogen combustion is prone to thermodiffusive instabilities largely dependent on differential diffusion, a phenomenon that can lead to higher probabilities of flashback in industrial burners, given hydrogen’s high reactivity and diffusivity. This paper evaluates low-swirl flames of methane and air enriched with hydrogen to highlight the onset of differential diffusion. Testing was conducted in a fully controllable swirl burner, where bulk velocity Uav = 13 m/s and swirl number S = 0.6 were kept constant for each hydrogen–methane blend to isolate increases in flame surface area from increases in turbulence intensity. Furthermore, each fuel blend of hydrogen and methane is evaluated at the same laminar flame speed of SLo = 0.267 m/s to isolate flame stretch effects on the turbulent burning rate. Combined hydroxyl (OH) PLIF and stereoscopic PIV at the National Research Council of Canada were used to analyze the OH fluorescence in a 2D-3C velocity field for each flame condition. High-speed PIV at McGill University was used to resolve local flame phenomena, such as local flame displacement velocity and flame stretch rate. Using these techniques, it can be observed that the flame displaces axially in response to turbulent flame speed while exhibiting increases in flamefront wrinkling. This increased corrugation due to flame stretch is highlighted in the PDFs of local curvature and κSf and is further evidenced by a shift towards positive curvatures (κ > 0) for increasing H2 volume fraction. This trend suggests that there is a strong correlation with increases in turbulent burning rate and positive curvature as a result of differential diffusion, but it is not necessarily a control mechanism of the most forward propagating points proposed by the theory of leading points.